Making Eco-enzyme Formulation for Students of SMAN 1 Larangan Brebes District Through Community Service: Pembuatan Eco-Enzyme Untuk Siswa Sman 1 Larangan Kabupaten Brebes Melalui Melalui Kegiatan Pengabdian Kepada Masyarakat - Aldi Budi Riyanta; Inur Tivani; Heru Nurcahyo (Universitas Lancang Kuning, 2023)
Law No. 18 of 2008 was enacted by the Government in the context of waste management. One of the waste in question is organic waste such as orange peel. In order to realize the activities of the tri darma and environmental-based “adiwiyat”a schools at SMA N 1 Larangan, community service activities related to the manufacture of eco-enzymes were held. This community service activity aims to increase knowledge about the processing of organic waste from orange peel into eco-enzymes in the form of training on making eco-enzymes to improve eco-enzyme-based waste treatment skills. The method of activities carried out includes preparation in the form of activities in the laboratory of DIII pharmacy Politeknik Harapan Bersama, implementation in the form of providing education and training to students and evaluation in the form of pre-tests and post tests to measure the increase in student knowledge. The results of this community service activity have been adjusted to the purpose of this service, namely to increase students' knowledge and skills by 58.6% based on a questionnaire survey shortly before and after the training activity for making eco-enzymes and processed products.